Attitude to business reality, perceived value creation and subjective norms: how they impact on students of higher learning institutions’ self-employment intentions in Malaysia - Wan Yusoff, Wan Fauziah; Kasim, Rozilah; Martin, David; Gafar, Mudashir (MCSER Publishing, 2015)
The modern-day economy demands dynamic real estate entrepreneurial professionals as graduates’ job placement are becoming more competitive. The purpose of introducing entrepreneurship education into the Malaysian Higher Learning Institutions (HLIs) is to boost the employability of the graduates but the realization of this purpose in some of the university’s programmes is still unclear. In this regard, this research employed the theory of planned behaviour to assess hypotheses of the role of attitude in business reality, perceived value creation perceptions and subjective norms in influencing the selfemployment intention of real estate management (REM) students. The hypotheses were tested using cross-sectional data from 408 REM students of the Malaysian public universities. The research findings reaffirmed that attitude to business reality and perceived value creation did play a significant role in explaining REM students’ self-employment intention while subjective norms had no significant impact. However, the role of attitude to behaviour in business reality acted to be more relevant. The implications of the research findings could impact educational policy, particularly, academic entrepreneurship education.